Novel 1′-homo-N-2′-deoxy-α-nucleosides: synthesis, characterization and biological activity. Issue 27 (21st April 2020) - Carnero, Alejandro; Martín-Nieves, Virginia; Sanghvi, Yogesh S.; Russel, Olivia O.; Bassit, Leda; Schinazi, Raymond F.; Fernández, Susana; Ferrero, Miguel
Abstract : Novel 1′-homo- N -2′-deoxy-α-nucleosides and dimers. Abstract : For the first time, a series of novel 1′-homo- N -2′-deoxy-α-nucleosides containing natural nucleobases as well as 5-fluoro and 5-iodopyrimidine analogs have been synthesized in an efficient manner. Additionally, a high yield protocol for the assembly of a dimeric scaffold containing two sugar moieties linked to the N -1 and N -3 positions of a single pyrimidine base has been accomplished. The structures of the novel homonucleosides were established by a single crystal X-ray structure of 1′-homo- N -2′-deoxy-α-adenosine and NMR studies. The biological activity of these 1′-homo- N -2′-deoxy-α-nucleosides as antiviral (HIV-1 and HBV) and cytotoxic studies was measured in multiple cell systems. The unique structure and easy accessibility of these compounds may allow their use in the design of new nucleoside analogs with potential biological activity and as a scaffold for combinatorial chemistry.